Therapeutic potential of Equisetum arvense L. for management of medical conditions - Amos Luanda; Asha Ripanda; John J. Makangara (Phytomedicine Plus, 2023)
Background: Equisetum arvense L. has a long history of use in traditional medicines for treating ailments like digestive, inflammatory, respiratory and urinary disorders. Researchers have been focused on developing drugs from natural sources particularly the medicinal plants for global mitigation of medical conditions while protecting the environment. The use of natural products is one of the strategies that the WHO recommended to manage global medical conditions. The interest to use natural remedies as alternative medicines for management of medical conditions is increasing considerably. Purpose: This review intended to discuss the therapeutic potential of E. arvense for the mitigation of various diseases by providing up-to-date information on its benefits, challenges and potential future opportunities. Methods: The information is collected and systematically analysed from various online databases including Google scholar, ScienceDirect, Springer, Web of Science, PubMed and Plant of the World Online. Results: This study demonstrated the enormous therapeutic potential of E. arvense for the management of various ailments. The significant changes in the phytoconstituents amongst the plant parts have been observed, which correspond to the variation in its pharmacological properties. Several pharmacological activities of E. arvense such as anticancer, anti-inflammatory, antibacterial, antifungal and antidiabetics support its traditional uses. Conclusion: E. arvense has a lot of therapeutic promises for treating a number of health disorders. The extension of its clinical study requires further identification of the bioactive compounds, their modes of action as well as toxicological study. The existing therapeutic potential of E. arvense, suggesting that it is a suitable medicinal plant for management of medical conditions.